2015
DOI: 10.3109/02770903.2015.1075549
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver education to promote appropriate use of preventive asthma medications: what is happening in primary care?

Abstract: Objective To describe actions taken by providers at primary care visits to promote daily use of preventive asthma medication, and determine whether patient or encounter variables are associated with the receipt of asthma medication education. Methods As part of a larger study in Rochester, NY, caregivers of children (2 to 12 years old) with asthma were approached before an office visit for well-child, asthma-specific, or other illness care from October 2009 to January 2013. Eligibility required persistent sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 36 publications
0
9
0
11
Order By: Relevance
“…A number of studies have revealed that WCC visits are key to introducing asthma education and for supporting best practices. [16][17][18] Regular assessments of asthma control in a nonemergency setting have a significant impact on asthma control. 19,20 In expert guidelines, it is recommended that children with asthma receive regular monitoring at least every 6 months.…”
mentioning
confidence: 99%
“…A number of studies have revealed that WCC visits are key to introducing asthma education and for supporting best practices. [16][17][18] Regular assessments of asthma control in a nonemergency setting have a significant impact on asthma control. 19,20 In expert guidelines, it is recommended that children with asthma receive regular monitoring at least every 6 months.…”
mentioning
confidence: 99%
“…Child care providers for preschoolers have been shown to have positive attitudes toward having children with asthma in their classrooms but lack confidence and resources to evaluate and treat asthma symptoms (11). Traditional models of educating parents of children with asthma have focused on the role of healthcare providers in the education delivery process; however, multiple research studies have shown that this is inadequate, particularly for low-income urban families (23). Additionally, this traditional model also assumes that either the parent or healthcare provider will provide the school with the necessary knowledge and skills to manage asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Nursing education for family caregivers is considered as a workable and effective intervention that directly improves their disease knowledge, physiological management abilities and psychological support skills to provide better care to patients[ 8 ]. Studies have shown this intervention plays an active role in the course of specific diseases including stroke[ 9 ], asthma[ 10 ] and kidney injury[ 11 ]. However, the effectiveness of care education for family caregivers of patients with RA has not been reported.…”
Section: Introductionmentioning
confidence: 99%